2010
DOI: 10.1002/jcp.22052
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of early‐response to mechanical stress in neonatal rat mandibular condylar chondrocytes

Abstract: The objectives of this study were to investigate the early response to mechanical stress in neonatal rat mandibular chondrocytes by proteomic analysis. To evaluate its molecular mechanism, chondrocytes were isolated and cultured in vitro, then loaded mechanical stress by four-point bending system on different patterns. Morphological observation, flow cytometric analysis, and MTT assays indicated that 4,000 microstrain loading for 60 min was an appropriate mechanical stimulus for the following proteome analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 76 publications
1
18
0
Order By: Relevance
“…Furthermore, many studies have indicated that cartilage thinning is important in the pathogenesis of TMJ diseases (14, 28 -31). Teramoto et al (14) demonstrated a significant decrease in the proliferation of condylar cartilage and the amount of extracellular matrix under compressive force, and we also previously demonstrated reduced proliferation of mandibular chondrocytes in response to mechanical stress in vitro (11). The results of the present study are consistent with these studies.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Furthermore, many studies have indicated that cartilage thinning is important in the pathogenesis of TMJ diseases (14, 28 -31). Teramoto et al (14) demonstrated a significant decrease in the proliferation of condylar cartilage and the amount of extracellular matrix under compressive force, and we also previously demonstrated reduced proliferation of mandibular chondrocytes in response to mechanical stress in vitro (11). The results of the present study are consistent with these studies.…”
Section: Discussionsupporting
confidence: 83%
“…This approach has been successfully utilized to examine chondrocyte differentiation and cartilage pathophysiology (9,10). Our previous study of the response of mandibular chondrocytes to mechanical stress in vitro demonstrated a transient but inhibitory effect on cell cycle progression, accompanied by cytoskeleton remodeling and MAPK pathway activation (11). However, the molecular mechanisms regulating mandibular cartilage responses to mechanical stress in vivo have not been thoroughly investigated, and the determinants mediating cartilage loss induced through mechanical stress remain largely unknown.…”
mentioning
confidence: 99%
“…Cyclic tensile strain (CTS) was applied to growth plate chondrocytes plated on culture plates by using the four-point bending system which has been characterized and described in detail elsewhere. 26 In brief, when cells had reached 80% confluence, the medium was changed to serum-free media and cultured for overnight, and the cells were exposed to CTS at a frequency of 0.5 Hz. The unstrained control group was cultured on similar plates and kept in the same incubator for the same time period.…”
Section: Application Of Cyclic Mechanical Strainmentioning
confidence: 99%
“…21 Under aseptic conditions, the cartilage was removed from the head of the condyle. In brief, the condylar cartilage was minced and digested with 0.25% trypsin and 0.2% collagenase, and then the chondrocytes were rinsed three times and prepared as a single cell suspension in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% foetal calf serum, 25 mM 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (HEPES), 1% L-glutamine, and 100 mg/ml kanamycin.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%